Foreign direct investment and economic growth: The role of financial development - My-Linh Thi Nguyen (Cogent Business & Management, 2022)
This study was conducted with the aim of examining the role of financial development in the impact of foreign direct investment on economic growth. The interesting point of this study is expressed through the effort to determine the level of financial development to maximize the spillover effects of foreign direct investment on economic growth, whereby financial development is measured through the development of the banking sector and the stock market. The data were collected from 6 countries of the Association of Southeast Asian Nations (ASEAN-6) in the period 2002-2019, including: Indonesia, Malaysia, Thailand, Singapore, the Philippines, and Vietnam. Regarding the method of analysis, this study uses threshold effects and system GMM to estimate research models. The estimation results show that there are threshold values of financial development through the banking sector (85.64%) and the stock market (21.95%). Furthermore, this study found a positive impact of foreign direct investment on economic growth in the regions before and after these threshold values. In particular, the positive impact of foreign direct investment on economic growth becomes stronger when financial development exceeds the defined threshold value. This result is found in the case where financial development is measured through both the banking sector and the stock market.
Keywords: G15; F43; F38; 650; economic growth; foreign direct investment; ASEAN-6; domestic credit; market capitalization